2004
DOI: 10.1021/ja047125e
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Foray into the Formation and Reactivity of Metallabenzenes

Abstract: Various metallabenzene complexes, analogues of benzene where one CH unit has been replaced by an organometallic fragment, have been reported in the literature. A detailed theoretical investigation on the chemistry of these complexes is presented here. This includes an evaluation of their aromaticity, the mechanisms of formation of osmium, iridium, and platinum metallabenzene complexes, and one intriguing aspect of their chemistry, the formation of cyclopentadienyl (Cp) complexes. X-ray photoelectron spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
126
0
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(140 citation statements)
references
References 109 publications
6
126
0
8
Order By: Relevance
“…Consistent with the mechanism calculated by Martin, van der Boom, and co-workers, [33] Elliott and Roper have found that the reaction of diphenylacetylene with [Os(CS)(CO)-(PPh 3 ) 3 ] produces the alkyne-substituted complex 42 and an osmacyclohexadienethione. [49] Unlike in the case calculated for acetylene, a second equivalent of diphenylacetylene does not add to generate the osmabenzene.…”
Section: Osmabenzofuransupporting
confidence: 76%
See 3 more Smart Citations
“…Consistent with the mechanism calculated by Martin, van der Boom, and co-workers, [33] Elliott and Roper have found that the reaction of diphenylacetylene with [Os(CS)(CO)-(PPh 3 ) 3 ] produces the alkyne-substituted complex 42 and an osmacyclohexadienethione. [49] Unlike in the case calculated for acetylene, a second equivalent of diphenylacetylene does not add to generate the osmabenzene.…”
Section: Osmabenzofuransupporting
confidence: 76%
“…[23,26] Recently, van der Boom, Martin, and co-workers calculated the energies of the various transition states in the formation of 1 by using model 6 as the starting complex to prepare 7 (Scheme 1). [33] Their study revealed that the first step in osmabenzene formation is loss of a phosphine ligand, followed by coordination to an acetylene molecule. The lowest-energy pathway was found to proceed by migratory insertion of the CS ligand into the s bond of the osmacyclopropene (Dewar-Chatt-Duncanson model).…”
Section: Osmabenzenesmentioning
confidence: 99%
See 2 more Smart Citations
“…因此, )的低端 [19] . 同 时 , 金 属 吡 啶 炔 所 在 六 元 环 的 核 独 立 化 学 位 移 [20] (NICS)值为 δ -4.5, 与已报道的金属苯的 NICS 值相 近 [21] . 因此, 结合化合物 …”
Section: 金属吡啶炔unclassified